Analytical Review on Acquiring Knowledge of Machining Capacities for Abrasive Flow - Prasad , Kanapala Rajendra (International Journal of Psychosocial Rehabilitation, 2020)
The abrasive flow machining technique utilizes a self-deforming device, an abrasive loaded media that is passed to and from in the entry geometry of the empty work piece with the help of two using pressurized water operated cylinders put inverse to one another. In the present work, the machining capacities of the abrasive flow machining and attractive abrasive flow machining have been analysed for Aluminium tubes using precisely alloyed attractive abrasives. It has been discovered that the percentage improvement in surface finish (PISF) is better in attractive abrasive flow machining when contrasted with abrasive flow machining.